Pelatihan Usaha Ekonomi Pembuatan Kerupuk Beras Desa Mekar Sari Kecamatan Narmada Kabupaten Lombok Barat - Dzakiyah Adila; Haerani; Aninda Astriana Safitri; Muhammad Safrullah; M. Azizul Mahaqi; Jannatul Laili Oktavia; Khaeril Azmi; M. Asyari; Ni Kadek Widianthari; Eka Puspitasari; Lilik Apriani (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Mekar Sari village has an region that is dominated by agricultural land and it has main agricultural products is rice. However, so far there are no further processing of these products so the economy value is still relatively low. For this reason, it is necessary to do further processing of products that made from rice with invasion and creativity that can increase the prices and develop community farming value products. Rice is a superior product in this village, one of the products made from rice and have intrest in community is rice crackers. The innovation applied to rice cracker products is by adding variants of flavor to rice crackers, so it is hoped that these products will be able to compete in the market. The training is carried out starting from the production process, packaging, to marketing. This training is carried out to produce rice crackers with a higher economy value which is expected to help improve the local community's economy.